A Coasian Model of International Production Chains - Fally, Thibault (The World Bank, 2015)
International supply chains require the coordination of numerous activities across multiple countries and firms. This paper develops a theoretical model of supply chains in which the measure of tasks completed within a firm is determined by parameters that define transaction costs and the cost of coordinating more activities within the firm. The structural parameters that govern these costs explain variation in supply chain length as well as cross-country variation in gross-output-to-value-added ratios. The structural parameters are linked to comparative advantage along and across supply chains. The paper provides an analytical treatment of trade and welfare responses to trade cost change in a simple two-country model. To explore the models implications in a richer setting, the model is calibrated to match key observables in East Asia, and the calibrated model is used to evaluate implications of changes in model parameters for trade, welfare, the length of supply chains, and countries relative position within them